Recent Advances in the Structural Biology of the Volume-Regulated Anion Channel LRRC8 - Kasuya, Go; Nureki, Osamu (Frontiers in pharmacology, 2022)
Members of the leucine-rich repeat-containing 8 (LRRC8) protein family, composed of five LRRC8A-E isoforms, are pore-forming components of the volume-regulated anion channel (VRAC), which is activated by cell swelling and releases chloride ions (Cl − ) or other osmolytes to counteract cell swelling. Although the LRRC8 protein family was identified as the molecular entity of VRAC only in 2014, due to recent advances in cryo-electron microscopy (cryo-EM), various LRRC8 structures, including homo-hexameric LRRC8A and LRRC8D structures, as well as inhibitor-bound and synthetic single-domain antibody-bound homo-hexameric LRRC8A structures, have been reported, thus extending our understanding of the molecular mechanisms of this protein family. In this review, we describe the important features of LRRC8 provided by these structures, particularly the overall architectures, and the suggested mechanisms underlying pore inhibition and allosteric modulation by targeting the intracellular leucine-rich repeat (LRR) domain.